Moderate excess alcohol consumption and adverse cardiac remodelling in dilated cardiomyopathy. Issue 8 (11th August 2021) - Tayal, Upasana; Gregson, John; Buchan, Rachel; Whiffin, Nicola; Halliday, Brian P; Lota, Amrit; Roberts, Angharad M; Baksi, A John; Voges, Inga; Jarman, Julian W E; Baruah, Resham; Frenneaux, Michael; et al.
Abstract : Objective: The effect of moderate excess alcohol consumption is widely debated and has not been well defined in dilated cardiomyopathy (DCM). There is need for a greater evidence base to help advise patients. We sought to evaluate the effect of moderate excess alcohol consumption on cardiovascular structure, function and outcomes in DCM. Methods: Prospective longitudinal observational cohort study. Patients with DCM (n=604) were evaluated for a history of moderate excess alcohol consumption (UK government guidelines; >14 units/week for women, >21 units/week for men) at cohort enrolment, had cardiovascular magnetic resonance and were followed up for the composite endpoint of cardiovascular death, heart failure and arrhythmic events. Patients meeting criteria for alcoholic cardiomyopathy were not recruited. Results: DCM patients with a history of moderate excess alcohol consumption (n=98, 16%) had lower biventricular function and increased chamber dilatation of the left ventricle, right ventricle and left atrium, as well as increased left ventricular hypertrophy compared with patients without moderate alcohol consumption. They were more likely to be male (alcohol excess group: n=92, 94% vs n=306, 61%, p=<0.001). After adjustment for biological sex, moderate excess alcohol was not associated with adverse cardiac structure. There was no difference in midwall myocardial fibrosis between groups. Prior moderate excess alcohol consumption did not affect prognosis (HR 1.29, 95% CI 0.73 to 2.26, p=0.38) during median follow-up of 3.9 years. Conclusion: DCM patients with moderate excess alcohol consumption have adverse cardiac structure and function at presentation, but this is largely due to biological sex. Alcohol may contribute to sex-specific phenotypic differences in DCM. These findings help to inform lifestyle discussions for patients with DCM.